Tax Series Training: Enhancing Accounting Teachers' Capacity to Deliver Updated Tax Education for Social Equity - Eliza Silviana Miftakh; Adrian Hartanto Darma Sanputra; Sulastri (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: The primary aim of this community engagement program is to enhance the professional competence of accounting teachers in the Tulungagung district through training on the latest tax updates, specifically related to PPh Article 21/ 26 of 2023. Method: The methodology includes problem identification, tax material training, tax calculation practice, and participant presentations. This training is designed to refresh teachers' knowledge in delivering dynamic and relevant tax materials aligned with evolving business needs. Practical Application: The practical applications include improving teachers' skills in delivering accurate and sustainable tax education, supporting the creation of a more inclusive and equitable education system. This aligns with efforts to achieve social equity, where a solid understanding of tax obligations equips students with the knowledge to fulfill their responsibilities as citizens. Conclusion: This training successfully enhances accounting teachers' professionalism, contributes to social equity, and supports the achievement of sustainable development goals in the education sector.